2018
DOI: 10.14740/jh381w
|View full text |Cite
|
Sign up to set email alerts
|

May-Thurner Syndrome: A Rare and Under-Appreciated Cause of Venous Thrombosis in a 18-Year-Old Healthy Female

Abstract: May-Thurner syndrome (MTS) is a rarely diagnosed vascular abnormality that typically presents in young adults. The anomaly arises from compression of the left common iliac vein between the right iliac artery anteriorly and the lumbar vertebral body posteriorly, resulting in lower extremity venous outflow obstruction and recurrent deep vein thromboses (DVTs). We report the case of a 24-year-old female with a long history of recurrent DVTs and pulmonary emboli (PE) despite full anticoagulation. A computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…5 Overall, MTS is estimated to be the cause of 2% to 5% of all deep vein thromboses, and multiple autopsy studies in randomized patients have revealed a prevalence of MTS between 14% and 32%. 6,7 A retrospective study showed 24% of patients who underwent computed tomography of the abdomen and pelvis without suspicion of vascular pathology had a high degree of compression in the iliac vein, which corresponds to the typical image that is presented in the MTS. 6 Other radiologic studies, specifically targeting patients with left lower limb thrombosis, reported an incidence of MTS of 22% to 76%.…”
Section: May-thurner Syndrome: An Underdiagnosed Entitymentioning
confidence: 75%
See 2 more Smart Citations
“…5 Overall, MTS is estimated to be the cause of 2% to 5% of all deep vein thromboses, and multiple autopsy studies in randomized patients have revealed a prevalence of MTS between 14% and 32%. 6,7 A retrospective study showed 24% of patients who underwent computed tomography of the abdomen and pelvis without suspicion of vascular pathology had a high degree of compression in the iliac vein, which corresponds to the typical image that is presented in the MTS. 6 Other radiologic studies, specifically targeting patients with left lower limb thrombosis, reported an incidence of MTS of 22% to 76%.…”
Section: May-thurner Syndrome: An Underdiagnosed Entitymentioning
confidence: 75%
“…6 Other radiologic studies, specifically targeting patients with left lower limb thrombosis, reported an incidence of MTS of 22% to 76%. More recent epidemiologic studies showed that 72% of MTS cases are diagnosed between the ages of 25 and 50, which is far from the age of the individuals included in the manuscript by Cohen et al 1,7,8 Most patients have no symptoms during their lifetime; therefore, some authors have proposed using the term "May-Thurner anatomy" in patients without hemodynamic significance and reserving the term "May-Thurner syndrome" for cases with the compromised venous flow and clinical symptoms. 6 Approximately 77% of patients with MTS develop iliofemoral deep vein thrombosis and 23% develop venous claudication, resulting in a major disease with significant costs to health systems.…”
Section: May-thurner Syndrome: An Underdiagnosed Entitymentioning
confidence: 99%
See 1 more Smart Citation